PERTANGGUNGJAWABAN PIDANA KORPORASI PADA PERSEROAN PERSEORANGAN - Martin Setiawan; Miftakhul Huda (Jurnal HUKUM BISNIS, 2023)
Government deregulation through Government Regulation in Lieu of Law No. 2 of 2022 has brought several implications to the business world, especially concerning the establishment of sole proprietorships. As this is a new development in the Indonesian business landscape, issues related to sole proprietorships lack sufficient comparative studies. This research aims to analyze and identify the mechanisms of criminal liability that can be applied to corporations within the context of sole proprietorships. A sole proprietorship is a legal entity with characteristics that combine elements of both corporations and individual ownership. The complexity of corporate criminal liability increases when applied to this legal structure. The implications of applying corporate criminal law to sole proprietorships require further examination due to the unique nature of sole proprietorships compared to regular corporations. The research methodology employed is legal research, utilizing a principled approach to law and utilizing primary and secondary legal sources. Normative data is obtained through an examination of regulations related to corporate criminal liability in sole proprietorships. Empirical data is derived from literature or journals authored by legal practitioners, academics, or corporate representatives. The results of this study reveal that corporate criminal liability within the context of sole proprietorships faces several challenges, including the identification of perpetrators and roles in corporate criminal activities, as well as the determination of proportionate sanctions. This study employs a general overview as one of the methods to draw conclusions. Further comprehensive research is needed to gain a deeper understanding of the complexities involved in the application of criminal liability to corporations within the unique context of sole proprietorships. Keywords : deregulation; corporation; PERPU; sole proprietorship; corporate criminal liability